Production of Sorption Active Polypropylene Fabrics with Sulfonic Acid Groups by Radiation-Induced Modification of Polymer Surface - Bondar, I.V.; Han, D.H.; Cho, H.K. (Хімія, фізика та технологія поверхні, 2010)
Sorption active material carrying sulfonic acid groups was synthesized by radiation-induced graft polymerization of styrene monomer onto the surface of non-woven polypropylene fabric followed by sulfonation of grafted polystyrene chains. The effect of the main experimental parameters on styrene grafting degree (absorbed dose, monomer concentration, reaction time) was investigated. It was found that sulfonation degree of the grafted polystyrene chains with 5% chlorosulfonic acid at room temperature depends on the reaction time and reaches 80% for the samples with a medium value of styrene grafting degree. Sorption active polypropylene fabrics with sulfonic acid group densities of 3.5–5 meq/g were obtained. Радіаційно-індукована прищеплювальна полімеризація стиролу на неткану поліпропіленову тканину з подальшим сульфуванням прищеплених ланцюгів полістиролу була використана для синтезу сорбційно-активного матеріалу. Проведено дослідження впливу основних експериментальних параметрів (поглинена доза, концентрація мономера, час реакції) на ступінь прищеплювальної полімеризації стиролу. Встановлено, що ефективність сульфування прищеплених ланцюгів полістиролу при кімнатній температурі в 5% розчині хлорсульфонової кислоти залежить від часу реакції і для зразків з середніми ступенями прищеплення досягає 80%. Були синтезовані сорбційно-активні поліпропіленові тканини з щільністю кислотних груп 3,5–5 мг-екв/г. Радиационно-индуцированная прививочная полимеризация стирола на нетканной полипропиленовой материи с последующим сульфированием привитых цепей полистирола была использована для синтеза сорбционно-активного материала. Проведено исследование влияния основных экспериментальных параметров (поглощенная доза, концентрация мономера, время реакции) на степень прививочной полимеризации стирола. Установлено, что эффективность сульфирования привитых цепей полистирола при комнатной температуре в 5% растворе хлорсульфоновой кислоты зависит от времени реакции и для образцов со средними степенями прививки достигает 80%. Были синтезированы сорбционно-активные полипропиленовые ткани с плотностью кислотных групп 3,5–5 мг-экв/г.